Larval abundance across the European eel spawning area: An analysis of recent and historic data. Issue 5 (26th June 2018) - Westerberg, Håkan; Miller, Michael J.; Wysujack, Klaus; Marohn, Lasse; Freese, Marko; Pohlmann, Jan‐Dag; Watanabe, Shun; Tsukamoto, Katsumi; Hanel, Reinhold
Abstract: The abundance and distribution of leptocephalus larvae of the European eel ( Anguilla anguilla, Anguillidae) were examined using ten historic and recent Sargasso Sea expeditions that were selected on the basis of having the largest number of sampling stations and highest catches. The surveys cover the period 1920–2014. Station data were recalculated to the same unit of larval density per unit area, and the irregular station positions were transformed to a regular spatial grid to allow calculation of comparable measures of abundance of the youngest (0+) leptocephalus cohort. The result is that the mean and maximum densities of 0+ leptocephali after 2007 on average have decreased by 70%–80% from the densities during the period before the drastic decrease in glass eel recruitment, which started in the 1980s. This is of the same magnitude as the change in spawning stock, if the total continental commercial landings are used as a proxy. In the same period, the glass eel recruitment in Europe has decreased by more than 95%. The conclusion is that a major cause for the recruitment decrease may be an increased leptocephalus mortality during the oceanic phase or a large geographic shift in glass eel arrival. Combining the survey data, the spatial distribution of 0+ leptocephali was concentrated south of the northernmost front in the Subtropical Convergence Zone, but high densities were also found far south of the front in the western part of the distribution area and leptocephali were present also north of the average frontal position.